Emphysematous gastritis: A case report (Indian Journal of Case Reports, 2020)
Emphysematous gastritis, a rare clinical entity is characterized by the presence of gas in the stomach wall. It is potentially fatal disease and usually presents with systemic toxicity. We are presenting a case of a young female who has presented to our emergency room with systemic signs and contrast-enhanced computed tomography abdomen was showing gas within the gastric wall. The patient was managed conservatively and subsequently discharged.